Biodiversity in Agricultural Landscapes: Inter-Scale Patterns in the Po Plain (Italy) - Gemma Chiaffarelli; Ilda Vagge (Diversity, 2025)
Agrobiodiversity decline depends on wider-scale landscape ecological traits. Studying inter-scale patterns helps in understanding context-specific farm-scale biodiversity issues and needs. In this study, we investigated the drivers of agrobiodiversity in four Po Plain sites (northern Italy), an intensively impacted agricultural district. Farm-scale floristic–vegetational indicators reflecting anthropic disturbance (biological forms, chorological traits, and maturity traits) were studied for their relationship with species richness and phytocoenosis α-diversity values. Their correlation with local- and extra-local-scale landscape ecology traits was also studied. Species richness and α-diversity were negatively related to floristic contamination and therophytes; they tended to increase with the Eurasiatic and phanerophyte ratio, suggesting a role of disturbance conditions on diversity values. Extra-local/local scale showed similar relationships with farm-scale floristic–vegetational traits; correlation was higher for local scale. Species richness and α-diversity tended to increase with higher landscape natural components, landscape diversity, biological territorial capacity, and connectivity. These landscape traits also tended to be positively related to Eurasiatic, hemicryptophyte, chamaephyte, phanerophyte, and maturity values, while they were negatively related to adventitious, wide distribution, aliens, and therophytes. Corridors’ ecological quality apparently influenced disturbance-related species amount. Maps representing these inter-scale biodiversity facets are provided (land-use-based support ecosystem service maps integrated with landscape diversity maps). The detected patterns orient context-specific multi-scale biodiversity support. They confirm the theoretical frameworks and should be validated on wider datasets to strengthen their representativeness.